Measuring the safety climate in an Australian emergency department. (September 2021) - Connell, Clifford J.; Cooper, Simon; Endacott, Ruth
Highlights: The Safety Climate Survey is a reliable measure of safety climate for use in the ED. Clinicians in an Australian ED do not perceive a strong climate of patient safety. Expert ED clinicians were less confident about the safety of their patients. Clinicians with less expertise possess traits which can improve ED patient safety. Abstract: Background: There are numerous intricate human, system and cultural factors that can impact upon the safe and effective implementation of patient safety systems (e.g. rapid response systems). Safety climate is one of these factors and is a measure of frontline healthcare workers' shared perceptions, behaviours, beliefs and attitudes towards the organisation's culture of safety. Safety climate scores are also associated with the frequency of errors and adverse events in the healthcare setting. However, there is little evidence regarding the relationships between attitudes to patient safety and staff characteristics such as emergency care expertise and experience. The aims of this study were to measure perceptions of the safety climate in an Australian metropolitan Emergency Department and examine relationships between safety climate perceptions and staff characteristics. Methods: The Victorian Managed Insurance Authority Safety Climate Survey was administered to all doctors (n = 44) and nurses (n = 119) at an Australian emergency department. Results: Completed surveys were received from 127 (78%) respondents, 25 (52%) doctors and 100 (84%) nurses. Reliability analysis showed very good internal consistency of all 43-items of the survey (α = 0.94). With the exception of stress recognition, nurses rated the organisation's commitment to patient safety higher than doctors in all remaining attitudinal domains ( p < 0.05). Both groups acknowledge that fatigue, increased workload and stress recognition negatively impacts upon patient safety. There was a significant trend for declining safety climate ratings related to participants' clinical competence level and experience across all domains except stress recognition ( p < 0.05). Conclusions: The Safety Climate Survey appears to be a reliable measure of patient safety climate for use in Emergency Departments. Emergency doctors and nurses did not perceive there to be a strong organisational commitment to patient safety in an Australian Emergency Department. Emergency Departments can provide a safer environment through genuine commitment to safety culture improvement which capitalises on the insights, intrinsic strengths and behaviours characteristic of the ED team's expertise and experience. This kind of commitment can positively influence the effectiveness of actions taken to minimise risk to patient safety and improve ED staff job satisfaction and effectiveness.